Quasars in the 4D eigenvector 1 context: a stroll down memory lane - Sulentic, Jack W.; Marziani, Paola (Frontiers in Astronomy and Space Sciences, 2015)
Recently some pessimism has been expressed about our lack of progress in understanding quasars over more than fifty year since their discovery. It is worthwhile to look back at some of the progress that has been made – but still lies under the radar – perhaps because few people are working on optical/UV spectroscopy in this field. Great advances in understanding quasar phenomenology have emerged using eigenvector techniques. The 4D eigenvector 1 context provides a surrogate H-R Diagram for quasars with a source main sequence driven by Eddington ratio convolved with line-of-sight orientation. Appreciating the striking differences between quasars at opposite ends of the main sequence (so-called population A and B sources) opens the door towards a unified model of quasar physics, geometry and kinematics. We present a review of some of the progress that has been made over the past 15 years, and point out unsolved issues.